The Influence of Entrepreneurship Learning Practices in Business Incubators on Interest in Entrepreneurship with Self-Efficacy as a Mediating Variable - Amalia, Nabila; Sudarmiatin; Wardana, Ludi Wishnu (Formosa Journal of Multidisciplinary Research, 2024)
This research addresses gaps in previous studies by exploring the role of entrepreneurial learning practices and self-efficacy as mediating variables in fostering entrepreneurship interest among MA students in Banyuwangi. The research findings underscore the positive correlation between entrepreneurship learning, self-efficacy, and increased interest in entrepreneurship among Business and Marketing students.In conclusion, this research contributes to bridging existing gaps in knowledge and offers practical insights for educational institutions, paving the way for the improvement of entrepreneurship programs, curriculum design, and the development of facilities to nurture entrepreneurship among MA students in Banyuwangi